Yogurt Susu Kambing Etawa (Capra aegagrus hircus) dengan Penambahan Daging Buah Alpukat (Persea americana mill.) Sebagai Minuman Fungsional - Purnami Wulan, Dian Fitria (Jurnal Natural Scientiae, 2024)
Yogurt is a drink resulting from fermented milk using lactic acid bacteria. Yogurt production using Etawa goat's milk (Capra aegagrus hircus) was chosen because its nutritional content is quite good and low in lactose. The addition of avocado (Persea americana mill.) flesh to yogurt is expected to increase antioxidant activity and vitamin E levels. This research aims to produce goat's milk yogurt with the addition of avocado flesh as a functional drink that is liked by consumers, has antioxidant activity, and has high levels of high total phenolics and rich in vitamin E. The method used in this research includes the production of yogurt without the addition of avocado flesh as a control yogurt and yogurt with the addition of avocado in various variants. Then sensory analysis was carried out using the hedonic test, analysis of total phenolic content using the Follin-Cicocalteu method, analysis of antioxidant activity using the DPPH method and analysis of vitamin E levels using a spectrometer. The research results showed that the control yogurt was white in color, in the form of a thick, semi-solid liquid, had a distinctive smell, a sour taste, a homogeneous consistency and had a pH value of 4.3–4.8. The results of the sensory analysis test of yogurt with the addition of 20% avocado flesh (Y1) was the product most preferred by the panelists based on the color and aroma attributes, while for the texture and taste attributes the panelists preferred 40% (Y2). The total phenolic compound, antioxidant activity, and vitamin E test results of goat's milk yogurt reached 91.2%, the more avocado flesh was added, the yogurt with the addition of avocado flesh increased significantly with the addition of avocado pulp concentration